Living Up to the Hype: How New Ventures Manage the Resource and Liability of Future-Oriented Visions within the Nascent Market of Impact Investing - Logue, Danielle; Grimes, Matthew (Academy of Management Journal, 2022)
Hype is a collective vision and promise of a possible future, around which attention, excitement, and expectations increase over time. Within nascent markets, hype can thus serve as a cultural resource by which entrepreneurs might encourage greater early stakeholder support and resources. And yet as hype-driven support couples with mounting temporal and categorical expectations, this can also limit ventures’ flexibility during the entrepreneurial process. Drawing on an inductive, longitudinal, and comparative study of three new ventures within the much-hyped nascent market of impact investing, we develop an emergent theory of hype management, illustrating the field organizing practices that give rise to different forms of social proof, thereby allowing new ventures sufficient flexibility to convert hype into a sustained entrepreneurial opportunity. Our account contributes directly to contemporary public conversations of hype by revealing how entrepreneurs might engage with and indeed live up to the hype surrounding nascent markets without succumbing to the deceit and disappointment typically associated with hype. Beyond this, our findings extend existing scholarship on entrepreneurship within nascent markets, the sociology of expectations, and the realization of distant futures.